HAMBATAN IMPLEMENTASI KEBIJAKAN HUTAN TANAMAN RAKYAT DI BATU AMPAR, PROPINSI KALIMANTAN BARAT - Ritabulan Ritabulan; Sambas Basuni; Nyoto Santoso; M Bismark (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2016)
Mangrove utilization as raw material for charcoal by the people ofBatu Ampar was classified as illegal action, since the raw materials were taken from protected forests. Conversely, the existence of production forest and Community-based Plantation Forest (HTR) schemes have not become a solution to these problems. The aim of the research is to determine the history of utilization permit of mangrove forests as a source of raw material for charcoal by community and to analyze the constraints of the HTR policy implementation in Batu Ampar. This research was using quantitative and qualitative approaches. The results showed that the efforts to legalize business by community had been undertaken several times, but often collide with policies related to the dynamics of change in the status and functions offorest area in Kubu Raya District. Barriers to implementation ofthe HTR were: (1) mangrove forest which have potential for mangrove utilization as charcoal's raw material was still constrained with its status and function as Protection Forest; (2) lack ofcommunity knowledge on the regulations; (3) low quality human resources and the absence ofstrict sanctions; and (4) most ofthe tasks and functions ofgovernment agencies have not been implemented.